Effect of Treasury Single Accounts (Tsa) on the Performance of Ministries, Departments and Agencies (Mda) in Nigeria - Ofor, Nkechi T.; Omaliko, Leonard Emeka; Okoli, Francis Chukwudi (Vysoké učení technické v Brně, Fakulta podnikatelská, 2017)
Purpose of the article: The policy on the Treasury Single Account (TSA) was institutionalized to hedge financial loopholes, promote transparency and prevent mismanagement of government’s revenue by unifying all accounts of the government and preventing mismanagement of revenues by those agencies that generate revenue. This study however, examines the effect of the TSA policy on the performances of federal government MDAs in Nigeria. Methodology/methods: The study relied basically on primary data which was obtained through questionnaire designed and administered to75 respondents drawn from the federal government ministries, departments, agencies and parastatals (MDA) within Anambra metropolis in the eastern part of Nigeria. Analysis was based on the Wilcoxon sign test. Scientific aim: This study aims to empirically establish through available statistics the effect of implementing TSA on the performance of government ministries, departments and agencies in Nigeria. Findings: The result of this research indicate that the institutionalization of TSA has significantly affected and improved the performance of federal government MDAs at 5% level of significance which goes further to confirm that treasury single account is capable of blocking financial loopholes in revenue generation and promoting transparency and accountability. Conclusion: The study concludes by recommending that since the adoption of TSA has significantly improved the performance of federal government ministries, departments and agencies (MDAs) in Nigeria, government should enforce the adoption of TSA and ensure that it is mandatory for all MDAs and parastatals in the country.
Keywords: Treasury Single Account; Ministries; Departments and Agencies